Chiropractic Intervention and the Control of Eye Movement in Children With Attention Deficit Hyperactivity Disorder: a Pilot Study - Cade, Alice Elizabeth (Auckland University of Technology, 2017)
Background: Attention Deficit Hyperactivity Disorder (ADHD) is a multifaceted brain-based disorder that is often associated with adverse changes in the capacity to control eye movements when tracking visual stimuli, otherwise referred to as oculomotor function. Sensorimotor integration, defined as the capability of the central nervous system to integrate different sources of stimuli in parallel and to transform such inputs into appropriate motor actions, is essential for proper oculomotor function. Previous research has shown chiropractic care alters sensorimotor integration in brain areas also thought to be responsible for some of the cognitive and oculomotor deficits exhibited by those with ADHD. Objectives: This study tested the implementation of all study processes. Secondary aims were to examine the preliminary efficacy of a chiropractic intervention, aimed at improving spinal function, on oculomotor outcomes in children with ADHD. Methods: Thirty children between 8-15 years were recruited for a randomised controlled crossover pilot study to test all study processes, including recruitment, data collection, and general study management. The study also investigated chiropractic intervention versus an active control intervention on measures of oculomotor outcomes. Oculomotor function was tested before and after each intervention using a computerised eye tracker that measured target acquisition, reading speed, fixation time, and saccade length. Results: The study proved successful in its procedural testing; participant recruitment was completed in eleven weeks, with 100% retention and zero drop-outs, the outcomes measured were a reliable indicator of oculomotor function, and not susceptible to participant’s effort, researcher influence or parental reporting bias. Additionally, 85-100% of participants and guardians agreed or strongly agreed with statements evaluating the study, an overwhelmingly positive response. However, 40% of participants were unable to complete some part of the pre or post intervention outcome measures due to equipment calibration issues. Future research or clinical trials are recommended, with some modification of the study’s processes (for example improved eye tracking equipment and study settings). Secondary findings revealed a significant reduction (p = .034) was observed in the total reading time post chiropractic intervention (mean reduction: 646.87ms) compared to post control intervention (mean reduction: 108.35ms). No significant group differences pre or post chiropractic or control intervention in target acquisition time or number of distractions off-target (p > .05). Conclusions: This study is a successful pilot for further research in the area of chiropractic and oculomotor outcomes, proving feasible in terms of recruitment, data collection, outcome measurements used, and ease of testing procedures. Additionally, this study’s secondary findings open up the possibility that chiropractic care may have a role in improving reading ability and oculomotor function.
Keywords: ADHD; Pilot study; Chiropractic; Oculomotor; Eye tracking; Child outcomes; Reading; Saccades; Fixations; Target acquisitions